Social imaginaries of security and crime in Chilean digital written press - Basulto Gallegos, Oscar (2025)
This article examines the social imaginaries regarding security and crime in two editorially contrasting Chilean online newspapers: El Mercurio Online (EMOL) and El Ciudadano. Through a qualitative comparative content analysis, the news coverage of both outlets during April 2023 is examined, addressing the differences and similarities in their approaches. These findings are also contrasted with previous research on the Social Outbreak and other previous social movements in Chile. Divergent approaches are identified: EMOL emphasizes punitive solutions and crisis narratives to insecurity, while El Ciudadano criticizes government management and highlights social inequalities. In this sense, both outlets highlight security as a central issue, but with differentiated mediatizations. The construction of media discourses that reinforce or challenge hegemonic social imaginaries regarding security and crime is evident, as well as the configuration of social perceptions and associated political decision-making.